Kewenangan Notaris Menjalani Jabatannya Pasca Putusan Pidana - Hardianti Z. Podungge (Officium Notarium, 2022)
This research examines the authority of a notary to carry out their position. The problems formulated are first, the implementation of the Notary's authority to serve their position after the criminal verdict. Second, the authority of the Notary Supervisory Board in imposing sanctions on a Notary who has been sentenced to a crime. The research method used is a normative legal research method with a case approach from the decision of the Supreme Court of the Republic of Indonesia Number 89/Pid.B/2020/PN Dps and laws and regulations. The gathering of the legal material uses literature and interviews techniques, while the analysis uses the normative qualitative technique. The results of the study conclude that first, the authority of a Notary to serve their position after a criminal verdict on probation for 1 (one) year is to be able to practice again as a Notary after being released from their sentence, the Notary can exercise their authority in accordance with article 15 UUJN. Second, the Notary Supervisory Board has the authority to impose sanctions on notaries who have been sentenced to criminal convictions. Third, the Regional Supervisory Board can conduct an examination of the findings of a notary who has been convicted of a crime by the District Court as an effort to supervise and guide the Notary so that they will act in accordance with the law and not commit any more criminal acts and will be recommended to the Regional Supervisory Council to be given sanctions according to the applicable regulationsKey Word: Authority of a Notary, Position of a Notary, Criminal Decision AbstrakPenelitian ini mengkaji tentang kewenangan notaris menjalani jabatannya. Masalah yang dirumuskan, pertama pelaksanaan kewenangan Notaris menjalani jabatannya setelah putusan pidana. Kedua, kewenangan Majelis Pengawas Notaris dalam memberikan sanksi kepada Notaris yang dijatuhi putusan pidana. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan kasus dari putusan Mahkamah Agung RI Nomor 89/Pid.B/2020/PN Dps dan peraturan perundang-undangan. Teknik pengumpulan bahan hukum menggunakan studi pustaka dan wawancara, sedangkan teknik analisa dan menggunakan kualitatif normatif. Hasil penelitian menyimpulkan, pertama, bahwa kewenangan Notaris menjalani jabatannya setelah putusan pidana atas putusan masa percobaan selama 1 (satu) tahun ialah dapat menjalankan praktek kembali sebagai Notaris setelah bebas dari hukumannya, Notaris dapat menjalankan kewenangannya sesuai pasal 15 UUJN. Kedua, Majelis pengawas Notaris berwenang dalam memberikan sanksi terhadap notaris yang dijatuhi putusan pidana. Ketiga, Majelis Pengawas Daerah dapat melakukan pemeriksaan terhadap temuan notaris yang dijatuhi pidana oleh Pengadilan Negeri sebagai upaya pengawasan dan pembinaan Notaris agar selanjutnya bertindak sesuai undnag-undang dan tidak melakukan tindak pidana lagi dan direkomendasikan kepada Majelis Pengawas Wilayah untuk diberikan sanksi sesuai ketentuan yang berlaku.Kata-kata Kunci: Kewenangan Notaris, Jabatan Notaris, Putusan Pidana